2021
DOI: 10.1186/s12868-021-00632-5
|View full text |Cite
|
Sign up to set email alerts
|

N/OFQ modulates orofacial pain induced by tooth movement through CGRP-dependent pathways

Abstract: Background Nociceptin/orphanin FQ (N/OFQ) has been revealed to play bidirectional roles in orofacial pain modulation. Calcitonin gene-related peptide (CGRP) is a well-known pro-nociceptive molecule that participates in the modulation of orofacial pain. We aimed to determine the effects of N/OFQ on the modulation of orofacial pain and on the release of CGRP. Methods Orofacial pain model was established by ligating springs between incisors and molars… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…CGRP is a neuropeptide found in the periodontal tissue and is responsible for promoting pain after surgery [ 53 ]. Studies have focused on regulating CGRP through targets such as TRPV1 and nociceptin/orphanin FQ [ 54 ]. Evidence-based medical research has also shown that high-frequency vibrations can accelerate orthodontic tooth movement by promoting the differentiation of osteoblasts, fibroblasts, and osteoclasts and increasing bone remodeling; thereby accelerating the process [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…CGRP is a neuropeptide found in the periodontal tissue and is responsible for promoting pain after surgery [ 53 ]. Studies have focused on regulating CGRP through targets such as TRPV1 and nociceptin/orphanin FQ [ 54 ]. Evidence-based medical research has also shown that high-frequency vibrations can accelerate orthodontic tooth movement by promoting the differentiation of osteoblasts, fibroblasts, and osteoclasts and increasing bone remodeling; thereby accelerating the process [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, unlike other members of the opioid family, nociceptin/orphanin FQ (N/OFQ) has been revealed to play bidirectional roles in the modulation of orofacial pain, exhibiting either pro-or anti-nociceptive effects. 45 Periodontal administration of UFP-101, a N/OFQ receptor antagonist, could alleviate orofacial pain induced by experimental tooth movement in rats, which suggested that periodontal N/OFQ receptors were involved in orofacial pain. 46 Subsequently, these investigators speculated that N/OFQ increased orofacial pain induced by tooth movement by upregulating CGRP.…”
Section: Substantial Experimental Evidences Suggest That Endogenousmentioning
confidence: 99%
“…46 Subsequently, these investigators speculated that N/OFQ increased orofacial pain induced by tooth movement by upregulating CGRP. 45…”
Section: Substantial Experimental Evidences Suggest That Endogenousmentioning
confidence: 99%
See 1 more Smart Citation
“…Orthodontic tooth movement upregulates the P2X3 receptor in the TG, while an inhibitor of P2X3 reduces orthodontic pain-like behaviors in rats ( 62 ). Orthodontic tooth movement in rats upregulates the nociceptin/orphanin FQ-opioid receptor-like receptor pathway in the TG, which exacerbates pain-like behaviors and likely mediates P2X3 upregulation in TG neurons ( 122 , 123 ). Interestingly, the exposure of mice to static magnetic fields decreases orthodontic pain-like behaviors, accompanied by a decrease in the expression of P2X3 ( 124 ), supporting the roles of P2X3 in orthodontic pain.…”
Section: Role Of Ion Channels In Periodontal Nociceptors In Orthodont...mentioning
confidence: 99%